Antibiotic subclasses differentially perturb the gut microbiota in kidney transplant recipients - Dong, Hanbo; Li, Runzhe; Zhao, Ni; Dadhania, Darshana M.; Suthanthiran, Manikkam; Lee, John R.; Ling, Wodan (Frontiers in Transplantation, 2024)
IntroductionThe impact of antibiotics on the gut microbiota in kidney transplant recipients is not well characterized. In this study, we determine the impact of different subclasses of antibiotics on the gut microbiota in a cohort of 168 kidney transplant recipients.MethodsGut microbiome profiling was performed on 510 fecal specimens using 16S rRNA gene sequencing of the V4-V5 hypervariable region. We classified fecal specimens by antibiotic exposure into 5 categories: Beta-lactam, Fluoroquinolone (FQ), Beta-lactam & FQ Group, Other Antibiotics, and No Antibiotic (No Abx). Mixed-effects regression models were utilized to identify changes in microbial diversity and in the centered log-ratio (CLR) transformed abundance of genera while adjusting for important covariates.ResultsAntibiotic administration was associated with a significant decrease in the Shannon alpha diversity index, a decreased abundance of 11 taxa including Eubacterium and Ruminococcus, and an increased abundance of 16 taxa including Enterococcus and Staphylococcus. Exposure to Beta-lactam antibiotics was associated with an increased abundance of 10 taxa including Enterococcus and a decreased abundance of 5 taxa including Eubacterium while exposure to FQ antibiotics was associated with an increased abundance of 3 taxa and a decreased abundance of 4 taxa including Ruminococcus.ConclusionsBeta-lactam antibiotics and FQ antibiotics have a profound impact on the gut microbiota in kidney transplant recipients. Given the link of the gut microbiota to infectious complications, antibiotic associated changes in the microbiota may lead to an increased risk for further infections.